(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad and his family all....And yet...Arabic rhetoric does not cease to provide us with possibilities to study it, because it was and still is a matter of controversy among scholars, past and present, and among these possibilities, in which a point of view can be presented, is the problem of arranging the chapters of truth and metaphor, and arranging the ranks of metaphor based on them. The rhetoricians looked at it and how they could differentiate between the forms of metaphor and arrange them in those ranks